Glial Fibrillary Acidic Protein Serum Levels Distinguish between Intracerebral Hemorrhage and Cerebral Ischemia in the Early Phase of Stroke. (6th January 2020) - Luger, Sebastian; Witsch, Jens; Dietz, Andreas; Hamann, Gerhard F; Minnerup, Jens; Schneider, Hauke; Sitzer, Matthias; Wartenberg, Katja E; Niessner, Marion; Foerch, Christian
Abstract: BACKGROUND: Recent studies have suggested that glial fibrillary acidic protein (GFAP) serum concentrations distinguish between intracerebral hemorrhage (ICH) and ischemic stroke (IS) shortly after symptom onset. In this prospective multicenter trial we validated GFAP in an independent patient cohort and assessed the quantitative relationship between GFAP release, bleeding size, and localization. METHODS: We included patients with a persistent neurological deficit (NIH Stroke Scale ≥4) suggestive of stroke within 6 h of symptom onset. Blood samples were drawn at hospital admission. GFAP serum concentrations were measured using an electrochemiluminometric immunoassay. Primary endpoint was the final diagnosis established at hospital discharge (ICH, IS, or stroke mimic). RESULTS: 202 patients were included (45 with ICH, 146 with IS, 11 stroke mimics). GFAP concentrations were significantly higher in ICH than in IS patients [median (interquartile range) 0.16 μg/L (0.04–3.27) vs 0.01 μg/L (0.01–0.01), P <0.001]. A GFAP cutoff of 0.03 μg/L provided a sensitivity of 77.8% and a specificity of 94.2% in distinguishing ICH from IS and stroke mimics [ROC analysis area under the curve 0.872 (95% CI, 0.802–0.942), P <0.001]. GFAP serum concentrations were positively correlated with ICH volume. Lobar ICH volumes were larger and thus associated with higher GFAP concentrations as compared to deep ICH. CONCLUSIONS: Serum GFAP was confirmed to be a biomarker indicating ICH in patients presenting with acute stroke symptoms. Very small ICH may be missed owing to less tissue destruction.